COMPENSATION MANAGEMENT OF EDUCATION - Iswan, Muhammad (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objectives of this research are to describe the compensation management in District Government of KutaiKartanegara that consists of planning compensation management, organizing compensation management, actuating compensation management, and controlling compensation management.The findings indicate that (1) Compensation management plan formulates the objectives and requirements that is to arrange employees, motivate improve performance, improve prosperity and spur and improve productivity and quality in providing services to the community and improve the orderly administration of local finance. (2) In Organizing, Procedure for the payment of additional income shall be made monthly, the procedure and the payment mechanism according to the prevailing laws and regulations. (3) Implementation of compensation management are the ongoing compensation process and compensation practice is provided. Requirements to be fulfilled by the employee in compensation (4) Control and evaluation shall be performed by each Regional Device Work Unit (SKPD) for employees through performance and attendance performance to identify the beneficiary in accordance with the data provided by each Regional Device Work Unit (SKPD) Keywords:Compensation, Management, Organization, Controlling